A Systematic Review of the Methods Used to Assess and Report Dietary Patterns - Wingrove, Kate; Lawrence, Mark A.; McNaughton, Sarah A. (Frontiers in Nutrition, 2022)
The use of dietary pattern assessment methods has increased over time. However, data from individual studies can be difficult to compare and synthesise when the dietary pattern assessment methods, and the dietary patterns that are identified are not described sufficiently. The aims of this systematic review were to analyse the application and reporting dietary pattern assessment methods, and the reporting of the dietary patterns that were analysed with health outcomes. Three electronic databases were searched (Medline, Embase, and Global Health). Cohort and nested case control studies published in English between January 1980 and March 2019 that examined associations between dietary patterns and health outcomes (including cardiovascular disease, cancer, diabetes and metabolic syndrome, and body weight) in apparently healthy, community dwelling adults (aged over 18 years) or children (aged 2-18 years) were eligible for inclusion. A narrative synthesis was conducted and descriptive statistics were used to summarise the application and reporting of each dietary pattern assessment method, and the reporting of the identified dietary patterns. Analysis of associations between dietary patterns and health outcomes was beyond the scope of this review. Of the included studies (n=410), 62.7% used index-based methods, 30.5% used factor analysis or principal component analysis, 6.3% used reduced rank regression, and 5.6% used cluster analysis. Some studies (4.6%) used more than one method. There was considerable variation in the application and reporting of dietary pattern assessment methods. For example, the application of Mediterranean diet indices varied in terms of the nature of dietary components (foods only or foods and nutrients) and the rationale behind the cut-off points (absolute and/or data driven). In some cases, important methodological details were omitted. The level of detail used to describe the dietary patterns also varied, and food and nutrient profiles were often not reported. To ensure dietary patterns evidence can be synthesised and translated into dietary guidelines, standardised approaches for the application and reporting of dietary pattern assessment methods and the reporting of the identified dietary patterns would be beneficial.